2019
DOI: 10.3390/molecules24244450
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites of The Endophytic Fungus Alternaria alternata JS0515 Isolated from Vitex rotundifolia and Their Effects on Pyruvate Dehydrogenase Activity

Abstract: The fungal strain Alternaria alternata JS0515 was isolated from Vitex rotundifolia (beach vitex). Twelve secondary metabolites, including one new altenusin derivative (1), were isolated. The isolated metabolites included seven known altenusin derivatives (2–8), two isochromanones (9, 10), one perylenequinone (11), and one benzocycloalkanone (12). Their structures were determined via 1D and 2D nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), and computational electronic circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…These natural mycotoxin products identified at level 2 are mainly novel and modified Alternaria mycotoxins. According to publications and database, , ALT, altenusin (ALU), desmethylaltenusin (DMA), desmethyldehydroaltenusin (DMDA), and altertoxin I were identified according to precursor and product ions, retention time, accuracy mass, and elementary composition. In our preliminary examination, Alternaria mycotoxins, secondary metabolites produced by Alternaria spp., exhibited a high response in negative ion mode.…”
Section: Resultsmentioning
confidence: 99%
“…These natural mycotoxin products identified at level 2 are mainly novel and modified Alternaria mycotoxins. According to publications and database, , ALT, altenusin (ALU), desmethylaltenusin (DMA), desmethyldehydroaltenusin (DMDA), and altertoxin I were identified according to precursor and product ions, retention time, accuracy mass, and elementary composition. In our preliminary examination, Alternaria mycotoxins, secondary metabolites produced by Alternaria spp., exhibited a high response in negative ion mode.…”
Section: Resultsmentioning
confidence: 99%
“…The enantiomer (+)-(12S,13R)-3, named alternatiol, has been isolated from Alternaria alternata JS0515 in 2019. 27 In this study, (−)-(12R,13S)-3 was reported for the first time and designated as (−)-alternatiol.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…As shown in Figure C, the absolute configuration of each isomer was determined by ECD calculation. The enantiomer (+)-(12 S ,13 R )- 3 , named alternatiol, has been isolated from Alternaria alternata JS0515 in 2019 . In this study, (−)-(12 R ,13 S )- 3 was reported for the first time and designated as (−)-alternatiol.…”
Section: Resultsmentioning
confidence: 86%
“…Perylenequinones 2 , 3 , 8 , and 15 showed excellent activities for inhibition of α-glucosidase in the range of 12–166 mM, being more potent than the positive control acarbose (427) . On the other hand, PQ 2 increased the activity of pyruvate dehydrogenase (PDH) in AD-293 human embryonic kidney cells (27.82 mM), and suppression of PDH activity is associated with various metabolic disorders such as obesity, diabetes, and cancer …”
Section: Biological Propertiesmentioning
confidence: 99%